2017
DOI: 10.1111/1365-2435.12816
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behaviours track transitions in seasonal phenotypes of female Siberian hamsters

Abstract: SUMMARY Seasonally breeding animals exhibit profound physiological and behavioural responses to changes in ambient day length (photoperiod), including changes in reproductive function and territorial aggression. Species where aggression persists when gonads are regressed and circulating levels of gonadal hormones are low, such as Siberian hamsters (Phodopus sungorus) and song sparrows (Melospiza melodia), challenge the well-established framework that gonadal hormones are important mediators of aggression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 68 publications
(181 reference statements)
4
27
0
Order By: Relevance
“…In addition to a shift in hormonal source, seasonal changes in steroid synthesis and metabolism within target tissues have been reported. For example, heightened steroid metabolism, including increased expression of the enzyme aromatase, which catalyses the conversion of T to E 2 , and elevated sensitivity to hormones (eg, E 2 ), such as increased expression of oestrogen receptors, within discrete brain regions, have been reported as key regulators of aggression in birds, 22,23 mammals, 24‐26 and species that display a sex role reversal in aggression 27,28 . Collectively, these mechanisms are consistent with the hypothesis that seasonal changes in aggression map onto changes in neuroendocrine processes; however, they do not describe, in turn, how aggression influences these processes.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition to a shift in hormonal source, seasonal changes in steroid synthesis and metabolism within target tissues have been reported. For example, heightened steroid metabolism, including increased expression of the enzyme aromatase, which catalyses the conversion of T to E 2 , and elevated sensitivity to hormones (eg, E 2 ), such as increased expression of oestrogen receptors, within discrete brain regions, have been reported as key regulators of aggression in birds, 22,23 mammals, 24‐26 and species that display a sex role reversal in aggression 27,28 . Collectively, these mechanisms are consistent with the hypothesis that seasonal changes in aggression map onto changes in neuroendocrine processes; however, they do not describe, in turn, how aggression influences these processes.…”
Section: Introductionmentioning
confidence: 77%
“…Throughout the study, hamsters were weighed on a weekly basis to track changes in body mass, and coat colour was assessed to document the transition from summer brown/grey to winter white 47,48 . In addition, oestrous cycles were monitored via vaginal cytology for all experimental animals 5 days prior to behavioural trials to determine whether females were cycling, as described previously 25,47‐49 . Hamsters were characterised as reproductively functional if they had functional reproductive tissues (ie, ovaries and uterine horns), displayed no significant change in body mass (≤ 10%) and maintained a brown/grey coat colour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gonadal steroids are known to promote aggression in numerous species [31], experiments have repeatedly shown that SD-housing increases, and gonadectomy has little to no effect on, aggression in adult male and female Siberian hamsters when tested in the resident-intruder paradigm [3236]. Instead, adrenal hormones have been proposed to regulate aggression in SD-housed Siberian hamsters [3739] and several other seasonal species [40].…”
Section: Discussionmentioning
confidence: 99%
“…For example, male cichlid fish rapidly transition to dominant physiological and behavioral phenotypes in response to social opportunities; Siberian hamsters ( Phodopus sungorus ) exhibit seasonal variation in aggression; and honeybees ( Apis mellifera ) transition through different social roles in the colony throughout the lifespan (Ben-Shahar, 2005; Maruska & Fernald, 2010; Maruska et al, 2013; Rendon et al, 2017; Robinson, 2002; Wen et al, 2004). These and many other examples suggest that the biological systems modulating social behavior exhibit functional plasticity across developmental, seasonal, and rapid neuromodulatory timescales in a species-specific fashion.…”
Section: Patterns Of Social Behavioral Variation In Naturementioning
confidence: 99%